2020
DOI: 10.3389/fpsyg.2020.01212
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Arabic Version of the Behavioral Intention to Interact With Peers With Intellectual Disability Scale

Abstract: According to literature, students' attitudes toward peers with disabilities are crucial for the social inclusion of students with disabilities. Therefore, knowledge about students' behavioral intention to interact with peers with intellectual disability (ID) can help improve the social inclusion of students with ID. This study aimed to examine the psychometric properties of the Arabic version of the Behavioral Intention to Interact with Peers with Intellectual Disability Scale (BIS). Data were collected from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…With regard to academic self-concept, multilevel analyses revealed that, unsurprisingly, students' SEN status and their ratings on their ratings of their teachers' DI practice contributed significantly as predictors. Consistent with previous research, the findings from this study indicate that students with SEN have a lower academic self-concept compared to their classmates without SEN (Venetz et al, 2015;DeVries et al, 2018;Knickenberg et al, 2019;Alnahdi and Schwab, 2020). A practical need addressed with this finding might be the great importance of using an individual reference standard orientation while providing feedback to students with SEN in inclusive classes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With regard to academic self-concept, multilevel analyses revealed that, unsurprisingly, students' SEN status and their ratings on their ratings of their teachers' DI practice contributed significantly as predictors. Consistent with previous research, the findings from this study indicate that students with SEN have a lower academic self-concept compared to their classmates without SEN (Venetz et al, 2015;DeVries et al, 2018;Knickenberg et al, 2019;Alnahdi and Schwab, 2020). A practical need addressed with this finding might be the great importance of using an individual reference standard orientation while providing feedback to students with SEN in inclusive classes.…”
Section: Discussionsupporting
confidence: 88%
“…In line with previous research, descriptive results further indicated that students reported relatively high ratings of school-wellbeing, social inclusion and academic self-concept (Alnahdi and Schwab, 2020;Schwab and Alnahdi, 2020;Zubriggen et al, 2021). However, high mean scores do not automatically imply that all students are reaching satisfying levels in their socio-emotional well-being.…”
Section: Discussionsupporting
confidence: 87%
“…However, to our knowledge, there is only one validated scale in Arabic for assessing attitudes toward intellectually disabled people (the Arabic version of the Behavioral Intention to Interact with Peers with Intellectual Disability Scale). 40 However, the two-factor scale, which measures behavioral intentions in and out of school, was designed to assess only student attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the FDI 4-6, Venetz et al (2014), therefore, developed the PIQ, a 12-item instrument that measures the three indicators of inclusive education from students' perspective. The questionnaire consists of Today, the instrument is used in different languages, cultures, and groups of students (e.g., Alnahdi and Schwab, 2020;Guillemot and Hessels, 2021;Schmidt et al, 2021;DeVries et al, 2022;Zwierzchowska et al, 2022). In addition to the student version (PIQ-S), versions for teachers (PIQ-T) and parents (PIQ-P) have been developed, which in turn can be deployed to assess the three dimensions relating to students from multiple perspectives (Schwab et al, 2020).…”
Section: The Perceptions Of Inclusion Questionnairementioning
confidence: 99%